2007
DOI: 10.1038/sj.npp.1301357
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Methadone Maintenance in Rats: Effects on Cocaine Self-Administration and Behavioral Side Effects

Abstract: It has been demonstrated that high-dose methadone maintenance is efficacious in reducing cocaine abuse in opioid-dependent individuals, but it is not clear whether this is caused by an action of methadone on the direct reinforcing properties of cocaine or on cocaine seeking. Also, it is not clear whether high-dose methadone maintenance may induce behavioral side effects, which could limit its clinical use. Here, we report that high-dose methadone maintenance (20-40 mg/kg/day) does not reduce, and even enhances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 83 publications
(99 reference statements)
2
13
0
Order By: Relevance
“…The expression of sensitized psychomotor activation has been associated with increased drug-seeking behavior in several studies (De Vries et al, 1998Vezina, 2004), suggesting episodic withdrawal during intermittent drug exposure may also promote relapse vulnerability. In contrast, continuous drug delivery during a period of withdrawal has been shown to reduce drug-seeking behavior in animal models (Leri et al, 2007(Leri et al, , 2004, consistent with the effectiveness of maintenance therapy for human drug addicts (Dole et al, 1966;Henningfield and Keenan, 1993). A role for episodic withdrawal in establishing vulnerability to relapse would complement evidence that spontaneous withdrawal may itself reinstate extinguished drug-seeking behavior (Shaham et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…The expression of sensitized psychomotor activation has been associated with increased drug-seeking behavior in several studies (De Vries et al, 1998Vezina, 2004), suggesting episodic withdrawal during intermittent drug exposure may also promote relapse vulnerability. In contrast, continuous drug delivery during a period of withdrawal has been shown to reduce drug-seeking behavior in animal models (Leri et al, 2007(Leri et al, , 2004, consistent with the effectiveness of maintenance therapy for human drug addicts (Dole et al, 1966;Henningfield and Keenan, 1993). A role for episodic withdrawal in establishing vulnerability to relapse would complement evidence that spontaneous withdrawal may itself reinstate extinguished drug-seeking behavior (Shaham et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…However, in our laboratory rats, motor sedation induced by doses equal or above 30 mg/kg/day SSM administered by SC mini pumps dissipate within a few hours from implantation of pumps. Furthermore, 2-4 days following mini pump surgery, animals on SSM display dose-dependent elevations, not decreases, in locomotion activity (Leri et al 2004) and normal lever pressing behavior (Leri et al 2007). Finally, we have reported that 30 mg/kg/day SSM administered via mini pump does not reduce behaviors motivated by food, and does not reduce basal dopamine concentrations in the NAc (Leri et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Total quantity of cocaine exposure achieved through conditioning with 1 mg/kg/inf is similar to levels achieved in rats that actively self-administered the same dose (Leri et al 2004). Thirty mg/kg/day methadone was used because this methadone dose has been previously shown to block cocaine induced reinstatement of cocaine seeking (Leri et al 2004), and to block formation and expression of cocaine place conditioning (Leri et al 2006) without producing general locomotor and other behavioral deficits (Leri et al 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Rats in experiment 7 and 8 were implanted with subcutaneous (SC) osmotic mini-pumps as previously described in Leri et al (2007).…”
Section: Surgerymentioning
confidence: 99%